Branched-chain amino acid transferase type 2 (BCAT2) deficiency: Report of an eighth case and literature review - Etienne Mondésert; Juliette Bouchereau; Manuel Schiff; Jean-François Benoist; Guilia Barcia; Boris Keren; Inès Mannes; Clément Pontoizeau; Charlotte Mansat; Apolline Imbard (Molecular Genetics and Metabolism Reports)
Branched-chain amino acid transferase type 2 (BCAT2) deficiency is a rare autosomal recessive genetic condition, with only seven cases described to date. It results in an elevation of branched-chain amino acid (BCAA) plasma concentrations, predominantly on valine, with normal concentration of plasma allo-isoleucine and urine branched-chain α-keto acids (BCKA). Despite this constant biochemical feature, clinical consequences remain unclear with heterogeneous and far less severe than maple syrup urine disease (MSUD) reported phenotypes, one individual being even asymptomatic.We report herein the eighth case of genetically confirmed BCAT2 deficiency, accompanied by a literature review and a discussion about the potential pathogenicity of this condition.An 11-year-old boy presented with a rapidly reversible initial acute neurological episode suggesting an epileptic seizure. Abnormalities on cerebral magnetic resonance imaging and suspicion of cognitive impairment led to further metabolic investigations. BCAT2 deficiency has been mentioned in front of increased BCAAs (valine = 1667 μmol/L, leucine = 701 μmol/L, isoleucine = 561 μmol/L). A homozygous novel nonsense variant on BCAT2 (c.34C > T, p.Arg12*) was found on whole exome sequencing. After oral pyridoxine supplementation (200 mg/day), a decrease in BCAA concentrations was observed (valine = 984 μmol/L, leucine = 462 μmol/L, isoleucine = 302 μmol/L).Laboratory and imaging findings were consistent with previously reported cases. However, clinical presentation of this case was atypical and could be related with epilepsy, although no other variant on epilepsy genes have been found. The relation between BCAT2 deficiency and these clinical findings is at this stage debated with regard to phenotypic variability. Further case-studies are needed to expand the knowledge about this condition.